Innovative application of sodium tripolyphosphate for the flotation separation of scheelite from calcite. (15th August 2021) - Wang, Xu; Jia, Wenhao; Yang, Congren; He, Rui; Jiao, Fen; Qin, Wenqing; Cui, Yanfang; Zhang, Zhengquan; Li, Wei; Song, Hao
Highlights: Sodium tripolyphosphate prevents the flotation of calcite. Sodium tripolyphosphate can improve the flotation separation efficiency of scheelite and calcite. Sodium tripolyphosphate is selectively adsorbed on the surface of calcite. A possible model of the flotation separation of scheelite from calcite is established. Abstract: The potential of sodium tripolyphosphate as a depressant for selective flotation separation of scheelite from calcite is investigated by the micro-flotation tests and industrial scale tests in this study. The depression mechanism of sodium tripolyphosphate is also studied by adsorption measurement, Zeta potential measurement and FTIR spectra. As suggested from the flotation test results, sodium tripolyphosphate have a good selective depression effect on calcite. The results of adsorption test, Zeta potential measurement, and FTIR spectra indicate that the selective adsorption of sodium tripolyphosphate on calcite surface hindered the further adsorption of FX-6 type sodium oleate (FX-6) on calcite surface, which prevented the flotation of calcite. However, the pretreatment of sodium tripolyphosphate have little effect on the subsequent adsorption of FX-6 on the scheelite surface, and scheelite still maintain good floatability. The selective adsorption of sodium tripolyphosphate occur between phosphate and Ca 2+ exposed on the calcite surface. Sodium tripolyphosphate have the potential to be used as an alternative calcite depressant to the flotation separation of scheelite and calcite.